Ekonomiczne miary efektywności kompresji danych - Swacha, Jakub (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Data compression allows for considerable reduction of data storage and transmission costs, measures proposed in the article make it possible to calculate savings for the most popular da compression applications. These measures may be used to estimate the profitability of implementing data compressi methods in company's information system, as well as to compare economic effectiveness technologically competitive solutions. An important advantage of the presented measures is that they may be used even if not all t cost-specific data is available. In that case, the calculated costs, though not so precise, will still useful. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 252-268